1999
DOI: 10.1300/j013v29n03_07
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptability of the Female Condom Among Substance-Using Women in Washington, DC

Abstract: This research is based on structured interviews, semi-structured interviews, and informal firsthand observation of women residents of Washington, DC who used crack and/or injected drugs during the previous 30 days. The study entailed introducing these women to the female condom, exposing them to an HIV risk reduction intervention teaching them how to use it and how to negotiate its use with their sexual partner(s). Women were tested for HIV and asked to return one week later for their results. They were asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Although women in the intervention group were more likely to insert a female condom 3 and 6 months after the intervention, relatively few women attempted to use it with a partner. The female condom has been found to have variable acceptability in the United States (Hirky et al 2003; Holmes et al 2008; Klein et al 1999; Sly et al 1997; Witte et al 1999), and there are a number of issues that may make it challenging for this population. Women with medication side-effects that include tremors or other movement disorders may find insertion of the female condom difficult.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although women in the intervention group were more likely to insert a female condom 3 and 6 months after the intervention, relatively few women attempted to use it with a partner. The female condom has been found to have variable acceptability in the United States (Hirky et al 2003; Holmes et al 2008; Klein et al 1999; Sly et al 1997; Witte et al 1999), and there are a number of issues that may make it challenging for this population. Women with medication side-effects that include tremors or other movement disorders may find insertion of the female condom difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Holmes et al (2008) showed that African American women without knowledge of the female condom were less likely to use it, but that women with multiple partners, high school education or more, and younger age, were more likely to use it. Qualitative and quantitative studies of women at high risk report that women liked the idea of perceived personal control and increased sexual pleasure for women and men associated with female condom use (Hirky et al 2003; Klein et al 1999). Physical discomfort on insertion and displeasing appearance were disadvantages (Hirky et al 2003; Klein et al 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As another example, introducing people to the female condom and educating them about its use may be another effective way to help people—particularly women—gain confidence in their ability to engage in safer sexual practices. To date, most studies on people’s experiences with the female condom have reported favorable results (Klein et al 1999; Shervington 1993; Van Deventer et al 2002), highlighting the value of this device as an intervention tool to elevate condom use self-efficacy. Educating ecstasy users how to use condoms correctly by teaching them proper condom inspection and application skills (e.g., check for expiration date, how to open a condom wrapper without damaging the condom, how to put on and remove a condom to reduce the risk of spillage, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Although data show that many women are interested in female-controlled HIV prevention methods (Gollub et al, 1995;Klein et al, 1999;Moon et al, 2000;Murphy et al, 2000), little information is available as to whether women most in need of alternatives to the male condom, such as women in violent relationships, are interested in and able to use these methods. In fact, several studies on acceptability of the female condom have found that the method is of greater interest and acceptability to women who are successful male condom users than to women unable to use male condoms and thus most in need of female-controlled methods (Cabral et al, 1999;Cecil et al, 1998).…”
Section: Introductionmentioning
confidence: 99%